2022
DOI: 10.1021/acsengineeringau.1c00031
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Facing Sustainable Visible Light Induced Degradation of Poly- and Perfluoroalkyls (PFA) in Water: A Critical Review

Abstract: Poly-and perfluoroalkyls (PFAs) are now designated as serious threats to the environment. More than 4700 PFAs, along with their precursors, show a high degree of persistence and long-range spreading in soils and waters causing recalcitrant bioaccumulation in plants, fish, birds, and mammals causing health hazards all along the food chain. Visible-light induced degradation of PFA in pure water using photocatalysts, a potentially sustainable advanced oxidation process, showed exciting results in laboratories fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…[ 104 ] There are reports showing PFAS photo‐oxidation with junctions between semiconductor and plasmonic materials with resonance within the excitation spectral range (See paragraph 5 and Table 2). However, the role of the metal plasmonic resonance is usually neither explicitly stated nor investigated [48a,57,107] . Indeed, several materials used as electron‐trapping media can absorb low‐energetic wavelengths to generate mobile excited charges that can recombine or be transferred either into the semiconductor or directly into the pollutant.…”
Section: Spectral Extension: Toward Exploitation Of Solar Lightmentioning
confidence: 99%
“…[ 104 ] There are reports showing PFAS photo‐oxidation with junctions between semiconductor and plasmonic materials with resonance within the excitation spectral range (See paragraph 5 and Table 2). However, the role of the metal plasmonic resonance is usually neither explicitly stated nor investigated [48a,57,107] . Indeed, several materials used as electron‐trapping media can absorb low‐energetic wavelengths to generate mobile excited charges that can recombine or be transferred either into the semiconductor or directly into the pollutant.…”
Section: Spectral Extension: Toward Exploitation Of Solar Lightmentioning
confidence: 99%
“…However, at the same time, the stable C−F bonds have made the degradation of these substances a challenge. 2 Due to the difficulty of their degradation and destruction, PFAS have earned the nickname "forever chemicals". Moreover, studies have shown that PFAS are environmentally detrimental, and potentially cause a range of health issues including thyroid illness, liver damage, and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The desirable properties of PFAS such as amphiphilicity, thermal stability, and resistance to oxidation result from their chemical composition; specifically, the strong C–F bonds, hydrophilic polar headgroup, and hydrophobic tail. However, at the same time, the stable C–F bonds have made the degradation of these substances a challenge . Due to the difficulty of their degradation and destruction, PFAS have earned the nickname “forever chemicals”.…”
Section: Introductionmentioning
confidence: 99%
“…In recent research, focused particularly on developing new visible-light active photocatalysts for the degradation of PFAS, bismuth oxyiodide (BiOI)–based semiconductor materials have received greater attention than more traditional titanium-, zinc-, and indium-based photocatalysts (Paul Guin et al 2022 ). The ability to absorb light in the visible region of solar spectrum and an increased mobility of photogenerated charge carriers by the induced dipoles of [Bi 2 O 2 ] 2+ slabs in BiOI increase its photocatalytic performance (Lin et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%